Managing knowledge within the manufacturing enterprise: An overview - Baxter, David; Roy, Rajkumar; Gao, James X. (Inderscience, 2009)
This paper examines the literature relating to manufacturing knowledge and describes how it contributes to the manufacturing enterprise. The review shows that there is a strong emphasis on design in the manufacturing knowledge research domain, and that detailed design is the main focus for current research. An analysis is carried out according to publication date and consequently trends are identified. The design focus is increasing, and the trends show that the domain is driven by industrial applications. The contribution to fundamental research in areas such as knowledge modelling is increasing. Areas that currently have little work in this domain include conceptual design and service.
Keywords: literature review; manufacturing knowledge; enterprise integration; knowledge management